(untitled) (Research, Society and Development, 2022)
The state of rest, called sleep, although natural and necessary for human beings, has become the reason for many problems in our modern society. Because the basic functions of sleep are uncertain, memory consolidation processes, cognitive development and sleep stages are targets of interest in scientific research, which relate these variables in the search to find common pathways in these physiological processes. In this systematic review, with the objective of evaluating the existence and relevance of a relationship between sleep deprivation and students’ memory, studies were analyzed and the information found on the relationship between sleep deprivation and students’ memory was compiled, Based on the data collected, it was possible to observe that there is a positive relationship between the variables studied among university students, that is, problems related to sleep generate negative impacts on students’ memory. However, further research is still needed in this area, so that it is possible to collect more accurate information, capable of generalizing the impacts of sleep on cognitive memory processes.